Kepatuhan Wajib Pajak Melalui Sosialisasi Perpajakan, Pelayanan Fiskus dan Sanksi Perpajakan - Ahmad Jaelani; Nurdhiana Nurdhiana; Wenny Ana Adnanti (Jurnal Ilmiah Aset, 2017)
This research aimed to find out the effect of tax socialization, fiscus service, and tax penalty on tax payers’ compliance at Kelurahan Tegalsari Candisari. The sample for this study were 90 tax payers. The analysis instrument used was by multiple linier regression. The result showed that tax socialization had no effect on personal tax payers’ compliance, while fiscus service had positive significant effect on personal tax payers’ compliance and tax penalty had positive significant effect on personal tax payers’ compliance.